Sensing ghosts and other dangerous beings: uncertainty, sensory deprivation, and the feeling of presence - Nenadalová, Jana (Religion, brain & behavior, 2025)
When alone in the darkness, humans often fear various “unseen others” like ghosts, monsters, burglars, or animals. In a laboratory study, we aimed to induce the feeling of presence (FoP) via uncertainty by setting participants into a sensory deprivation context and experimentally priming them with the information that another person may enter the room. Grounded in the predictive processing framework, we hypothesized that FoP would occur and increase with participants’ uncertainty (due to insufficient exteroceptive data input) and with experimental manipulation of prior expectations connected to the presence of other agents. We sampled 126 participants and recorded their experiences during a 30-minute-long sensory deprivation period using questionnaires, physiological signals, and semi-structured interviews. We observed that while uncertainty was positively associated with FoP, experimental priming showed no clear associations, and the associations with psychological dispositions were mixed.